Produksi Benih Sebar Varietas Padi dan Penyebarannya di Provinsi Banten - Angelita Puji Lestari; Ahmad Fauzan; Dwi Fitriani; Asep Sutiawan; Eka Yuli Susanti (Mahesa Research Institute, 2023)
The use of superior rice varieties is needed in an agricultural production system. Seed availability is still dominated by popular varieties, so it is necessary to disseminate new superior varieties through seed production activities. The aim of the rice seed production is to produce extension seed (ES) and distribute quality and certified the seed in Banten Province. The implementation of seed production activities is carried out on IP2TP BPSIP Banten land and farmer's land in the form of cooperation with farmer groups or breeder farmers. Quality testing and certification are carried out by BPSB Banten Province. Location of seed production activities in IP2TP covering an area of 3.05 ha consisting of Mantap, Inpari 43, and Inpago 13 varieties. Furthermore, collaborative activities with farmers in the Tirtya Jaya farmer group, Sawahluhur, Kasemen, Serang City covering 1 ha of Inpari 32 variety, Jamblang farmer group Marga Mulya Village, Mauk, Tangerang, covering an area of 5 ha for the Inpari 43 and Inpari 48 varieties and the Pasir Haleuang farmer group, Tambakbaya Village, Cibadak, Lebak, covering an area of 2 ha for the Inpari 48 variety. The activity achievements of the extension seed production have reached 21,370 kg. Seed distribution has been carried out in Lebak, Pandeglang, Serang, Tangerang, Serang and Cilegon as much as 17,982 kg.